Uchwały Związku Pisarzy Polskich na Obczyźnie – stosunek emigracji do kraju - Moczkodan, Rafał (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2020)
The study is devoted to discussions taking place around the three resolutions of the Polish Writers Association in Exile, serving émigré writers as a community. These, passed the first resolution in 1947, calling for a refusal to work with Polish publishing houses and literary periodicals. This evoked a lively discussion, which took on another life in 1956 when the Association, distancing itself from the changes taking place in October 1956 in Poland, renewed its resolution, taking an uncompromising stand against the communist authorities in Poland. The second round as it were of the polemic revealed that the majority of writers in exile were in favour of making use of the possibility to publish their work in Poland. In the end, the Polish Writers Association in Exile tempered its stand on this matter and in the third resolution left such decisions up to individual writers to decide.
Resolutions of the Polish Writers Association in Exile – Emigre’s Attitudes to Poland